Pelatihan Manajemen Usaha Dan Pemasaran Kelompok Tani Hutan Di Sekitar Tahura KGPAA Mangkunegoro I Ngargoyoso Karanganyar - Any Setyarini; Adijati Utaminingsih; Rohmini Indah Lestari; Emaya Kurniawati (CV. Multi Kreasi Media, 2025)
Business Management and Photography Techniques Training for the Lumintu Berkah Forest Farmers Group in Segorogunung Village, Ngargoyoso District, Karanganyar Regency, aims to improve members' skills in managing their eco-tourism campsites and agricultural businesses, as well as increasing their understanding of photography techniques for digital promotional purposes. This program is part of the implementation of cooperation between LPPM USM and DLHK Central Java Province. The training focused on managing eco tourism businesses, natural photography techniques, and the use of social media, especially Instagram, as a marketing tool. With 20 participants, this training not only provided new insights into business management and marketing strategies, but also trained them to produce attractive visual content for promotions. The results of the evaluation showed that the participants' business management skills and photography techniques had improved significantly. This program is expected to help forest farmer groups to more optimally manage their businesses, as well as introduce their products and services to the wider community through digital platforms.